The Darkest Hue (Instagram, 2021)
"Jeymes Samuel isn’t much more imaginative than white Hollywood writers and directors. He can’t imagine Stagecoach Mary looking how she did- a beautiful fat, tall, dark-skinned Black woman- and being desired. His casting choices may reflect his *gendered* colorist biases. He hand-picked dark-skinned, monoracial Black actors to play the big, strong, and tough cowboys, despite most of the real-life male characters being fair-complected and mixed-raced. The first person he chose to be Stagecoach Mary was Erykah Badu, a light-brown skinned, thin, and green-eyed Black woman in his 2013 short film They Die by Dawn. He recently chose Zazie Beatz, a light-skinned biracial actress, to play Stagecoach Mary. This infographic essay explores what could have informed these decisions. Light skinned and biracial actresses also have a responsibility to turn down these roles (see slide 9). Don't forget to support me (last slide) if you're able to! #colorism #stagecoachmary #zaziebeetz #thehardertheyfall #jeymesamuel #explorepage #explorepage"
Keywords: 2000 à aujourd'hui; approches et analyses; colorisme; corps; cours; fem3300; intersectionnalité; militance; premier cycle; périodes historiques; racisme; ressource en ligne; sexisme; systèmes d'oppressions; thématiques; violences

Feu!: abécédaire des féminismes présents - Dorlin, Elsa (Libertalia, 2021)
Plutôt que de réduire le féminisme à des revendications faites à l’État, au patron, au chef ou à papa, pour plus de lois, plus de “sécurité”, à n’être que le porte-drapeau ou le cache-misère du capitalisme, de tel ou tel gouvernement nationaliste, ces histoires des féminismes présents rappellent et font résonner ensemble nos vies féministes. Ce livre fonctionne comme un abécédaire, un manuel, une boîte à outils, un dictionnaire amoureux, dans lequel échanger des idées, affûter des armes, écouter des voix, partager des expériences et des pratiques, vibrer pour des luttes présentes. Il s’adresse à tous·tes : il contient à la fois des ressources et foisonne de références utiles, de notions, mais il est fabriqué par des plumes et des voix, des points de vue situés sur des retours d’expériences collectives, des itinéraires politiques et intimes, des réflexions et des rétrospections sur des parcours, des engagements, des révoltes et des espoirs. En pluralisant les styles, en se situant à la fois du côté de la théorie et de la pratique, de la création, des écritures au “nous” et au “je”, il témoigne de la force d’une approche féministe de l’histoire intellectuelle et politique. Il est dédié à toutes les résistantes anonymes au quotidien des violences les plus crasses, à celles qui embrasent les tribunaux, cassent des genoux et brisent les vitrines, à celles qui inventent mille tactiques imperceptibles pour survivre et se mettre à l’abri, à la mémoire de celles dont les noms recouvrent les murs de nos villes la nuit, à la puissance des collectifs qui se font, à ceux qui se sont défaits, qui se sont (re)constitués ailleurs ou autrement, à ce qui nous lie.
Keywords: afro-féminisme; approches et analyses; corps; cours; droits des femmes*; fem3100; féminisme décolonial; féminismes noirs; genre; identités LGBTQIA2+; intersectionnalité; inégalités; outils; ouvrages de références; premier cycle; queer; racisme; sex2283; sexisme; sexualité; soc2014; systèmes d'oppressions; thématiques; violences; écoféminisme

Futurs & Projections (FéminÉtudes, 2021)
FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; corps; féminétudes; genre; identités LGBTQIA2+; intersectionnalité; militance; personnes trans*; périodes historiques; queer; québec; régions géographiques; sexualité; thématiques; violences; écriture des femmes*

Genre, rap et enjeux de la visibilité dans l'espace public des rappeuses à Montréal - Lesacher, Claire (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Cet article, basé sur une enquête de terrain menée en 2011, à Montréal, porte sur les enjeux qui traversent la question de la présentation physique des rappeuses dans l’espace public. Au cours des entretiens, les rappeuses soulignent que les activités de médiatisation et de représentation sur scène impliquent de devoir composer avec des représentations situées de la féminité dans un contexte où les industries musicales et médiatiques favorisent leur visibilité d’abord en tant que femmes, ce qui a des effets sur leur reconnaissance/légitimité en tant qu’artiste. Cette étude jette un regard sur les processus qui s’organisent dans une activité rap majoritairement masculine, elle-même durablement évincée des espaces dominants de production et de médiatisation de la musique au Québec.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; chanson; corps; femmes* artistes; féminisme matérialiste; genre; intersectionnalité; montréal; périodes historiques; québec; rapports sociaux de sexe; représentations du corps; ressource en ligne; régions géographiques; thématiques; étude qualitative

Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Social vulnerability and the impact of policy responses to COVID‐19 on disabled people - Mladenov, Teodor; Brennan, Ciara Siobhan (Sociology of Health & Illness, 2021)
In this paper, we propose a conceptual framework for understanding the impact of the policy responses to COVID-19 on disabled people. These responses have overwhelmingly focused on individual vulnerability, which has been used as a justification for removing or restricting rights. This suggests the need to shift the attention towards the social determinants of disabled people's vulnerability. We do this by bringing literature on social vulnerability in disaster risk management or 'disaster studies' in contact with key concepts in disability studies such as the social model of disability, independent living, intersectionality, and biopower. Empirically, we draw on the findings of the global COVID-19 Disability Rights Monitor (www.covid-drm.org), as well as on reports from academic journals, civil society publications, and internet blogs. We put the proposed conceptual framework to work by developing a critical analysis of COVID-19 policies in three interrelated areas-institutional treatment and confinement of disabled people, intersectional harms, and access to health care. Our conclusion links this analysis with strategies to address disabled people's social vulnerability in post-pandemic reconstruction efforts. We make a case for policies that address the social, economic, and environmental conditions that disproportionately expose disabled people to natural disasters and hazards.
Keywords: approches et analyses; capacitisme; corps; covid-19; discipline; intersectionnalité; ressource en ligne; santé; sciences humaines; sociologie; soins de santé; systèmes d'oppressions; thématiques; vulnérabilité

Féminismes et pop culture - Padjemi, Jennifer (Points (Paris); 5721; P5721, 2021)
"Dans un essai passionné et engagé, Jennifer Padjemi explore l'alliance, pour le meilleur et pour le pire, des féminismes et de la pop culture. A partir des mouvements féministes modernes, elle décortique le rapport que nous entretenons avec les objets culturels les plus populaires. En utilisant la pop culture comme un miroir de notre société mondialisée, l'auteure interroge les liens d'interdépendance entre consommation de masse et idéologie progressiste, et jette un regard joyeux et lucide sur nos divertissements, sans concession au patriarcat."--Quatrième de couverture.
Keywords: afro-féminisme; approches et analyses; care; communication; corps; cours; discipline; féminisme afropéen; féminisme pop; féminismes noirs; intersectionnalité; journalisme; premier cycle; sex2283; sexualité; thématiques; écriture des femmes*; études culturelles

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap